Empowering Eritrean refugees in Sudan through quality education for sustainable development - Mohamed Osman, Gamal; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2019)
Quality education is one of the seventeen goals of the United Nations’ Sustainable Development Goals (SDG) agenda. The purpose of SDG4 is to ensure inclusive and equitable quality education and promote lifelong learning. One of the SDG4 targets is by 2030, substantially increase the number of youth and adults who have relevant skills, including technical and vocational skills, for employment, decent jobs and entrepreneurship. The aim of this paper is to propose a conceptual business model on how International Islamic University Malaysia (IIUM) can contribute to the global communities’ wellbeing through humanising education, aligned with SDG4, and SDG8. This paper adapted the design thinking and system thinking approach to solving the Eritrean refugee’s problems in Sudan through understanding their needs by building and developing business modelling tools such as Business model canvas (BMC) and Value proposition design canvas (VPC). The approach includes conducting a literature review and interviews for understanding the key problems; formulating and ideating business model options in solving the problems; validation of the business model by interviewing the customer segments. The sample size for the interview is 10 Students, 5 Teachers, 2 Donors, and 5 Volunteers. However, the main contribution of this paper is empowering the refugees with knowledge, values and skills to live productive, fulfilling and independent lives. The proposed solutions include educational skills such as technical skills programmes, Study materials, literacy programs, and mentoring programmes. This paper presents a sustainable business model that develops a long term relationship with several stakeholder groups.